2009
DOI: 10.1159/000229303
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Interaction in Cochlear Implant Recipients: Comparison of Straight and Contour Electrode Arrays

Abstract: The degree of overlap among cochlear nerve fibers stimulated by different electrodes results in electrode interaction, which has been shown to have a significantly deleterious effect on speech recognition performance in multi-electrode cochlear implant users. The Nucleus CI24R(CS) Contour array, which lies substantially closer to the modiolus than the CI24M straight array, is expected to exhibit narrower excitation patterns. The neural response telemetry (NRT) 3.0 software provides a method of measuring the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…Some authors recommend the use of perimodiolar arrays instead of straight arrays to favor a reduced NRT threshold. However, previous studies showed that perimodiolar placement of electrodes has no effect on NRT thresholds [ 24 , 25 ], an observation consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
“…Some authors recommend the use of perimodiolar arrays instead of straight arrays to favor a reduced NRT threshold. However, previous studies showed that perimodiolar placement of electrodes has no effect on NRT thresholds [ 24 , 25 ], an observation consistent with our study.…”
Section: Discussionsupporting
confidence: 93%
“…This might have clinical implications, since a medial array position is associated not only with lower stimulation currents but also with lower psychophysical thresholds and comfortable levels [Runge-Samuelson et al, 2009]. Contour arrays were designed to reduce the distance between the electrodes and the nerve endings and to maximize the quality of electrophysiological interaction be-tween these two structures [Xi et al, 2009]. This concept was supported by reports showing a relation between array location in the cochlea and its insertion depth on the one hand and speech recognition performance on the other [Finley et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies comparing perimodiolar and lateral wall electrode arrays in terms of eCAP measurements often failed to confirm lower eCAP thresholds for the perimodiolar electrode arrays. 19 , 20 , 21 , 22 The differences in the current amplitude or the distance between the electrode and the cochlear middle wall were often not statistically significant. One reason is a small patient size in such studies.…”
Section: Discussionmentioning
confidence: 99%